Creativity of Elementary School Students Based on The Description Text Writing Skill - Hajjah Rafiah; Sopia; Dina Huriaty (Program Studi Pendidikan Guru Sekolah Dasar, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah Malang, 2021)
Unique ideas in writing the description text can foster creativity for students, where one of the goals of writing is to train creativity through writing habits. Therefore, the purpose of this study was to describe the creativity of elementary school students based on their ability to write descriptive text. This research was a qualitative descriptive study with data collection procedures through tests and interviews. The subjects of this study were three of fifth grade students of SDN 1 Sei Teras Kapuas Kuala, each of whom wrote good, fair, and poor. Each category analyzed to determine their level of creativity. The results showed that students with good description text categories fulfilled the high level of creativity, the students with fairly description text categories and poorly description text categories fulfilled the medium level of creativity.